Choosing a Higher Education destination: Marketing of where, why and how? - Collins, Aye; Simsek, Hasan; Takir, Aygil (Routledge Journals, Taylor & Francis Ltd, 2022)
This study attempts to contribute to marketing services in higher education literature through the relationship between international students' satisfaction with educational experiences and the necessary adjustments by institutions to augment their services. It also aims to make theoretical contributions by understanding the international students' satisfaction criteria for university selection and enrolment. The findings of the study offer administrative implications for universities as well, regarding how they could appeal to international students by emphasizing components of institutional branding via online and offline marketing communication tools. Quantitative methodology was employed and data was collected through a survey. Sampling strategy was voluntary participation and 197 international students replied to the survey. Findings indicate that international students use personal contacts and social relations in finding international higher education institutions. Further, international students care about the campus culture (safe or not), the physical infrastructure of the university and library resources provided to students.
Keywords: International students; student recruitment; international higher education; satisfaction of international students; Turkey